The second Fermi large area telescope catalog of gamma-ray pulsars - Abdo, A.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M.; Bastieri, D.; Bellazzini, R.; Bhattacharyya, B.; Bissaldi, E.; Bloom, E.; et al. (Institute of Physics Publishing, Inc., 2013)
This catalog summarizes 117 high-confidence 0.1 GeV gamma-ray pulsar detections using three years of data acquired by the Large Area Telescope (LAT) on the Fermi satellite. Half are neutron stars discovered using LAT data through periodicity searches in gamma-ray and radio data around LAT unassociated source positions. The 117 pulsars are evenly divided into three groups: millisecond pulsars, young radio-loud pulsars, and young radio-quiet pulsars. We characterize the pulse profiles and energy spectra and derive luminosities when distance information exists. Spectral analysis of the off-peak phase intervals indicates probable pulsar wind nebula emission for four pulsars, and off-peak magnetospheric emission for several young and millisecond pulsars.We compare the gammaray properties with those in the radio, optical, and X-ray bands.We provide flux limits for pulsars with no observed gamma-ray emission, highlighting a small number of gamma-faint, radio-loud pulsars. The large, varied gamma-ray pulsar sample constrains emission models. Fermi’s selection biases complement those of radio surveys, enhancing comparisons with predicted population distributions.